2020
DOI: 10.3390/agronomy10020307
|View full text |Cite
|
Sign up to set email alerts
|

Initial Development of Corn Seedlings after Seed Priming with Nanoscale Synthetic Zinc Oxide

Abstract: Nanofertilizers are increasingly explored for sustainable micronutrient delivery in agriculture. Pre-treating seeds with nanofertilizers prior to planting (i.e., seed priming) reduces concerns about nanoparticle (NP) fertilizer non-target dispersion; however, priming formulations and concentrations must be carefully selected to avoid germination inhibition and toxicity. Here we investigate changes in corn seed germination and seedling development after seed priming with ZnO NPs, ZnO bulk and ZnCl2. To evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 27 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…A higher percentage of germination and seedling growth of wheat with the application of ZnO NPs has been reported by Solanki and Laura [11]. Neto et al [10] reported similar findings where ZnO NP application promotes an increase in maize germination and vigor up to a threshold concentration, after which, increasing concentrations provide diminishing benefit.…”
Section: Field Emergencesupporting
confidence: 71%
See 1 more Smart Citation
“…A higher percentage of germination and seedling growth of wheat with the application of ZnO NPs has been reported by Solanki and Laura [11]. Neto et al [10] reported similar findings where ZnO NP application promotes an increase in maize germination and vigor up to a threshold concentration, after which, increasing concentrations provide diminishing benefit.…”
Section: Field Emergencesupporting
confidence: 71%
“…Aside from its influence on crop growth, development and productivity, plant nutrition with Zn plays a key role in the germination, emergence of seedlings and establishment of population. These effects promoted by Zn are directly linked to the functions of this element in the plants protein synthesis, cell elongation, auxin biosynthesis, used in the gene expression, resistance to stresses and pollen formation [9][10][11]. Hence, the assessment of the impacts of ZnO NPs on the plant traits of wheat could provide new insights into the application of nanotechnology in improving the yield traits of wheat.…”
Section: Introductionmentioning
confidence: 99%
“…This response is thought to be mainly due to aggregation phenomena, interfacial interactions, and cellular responses, resulting in a nonlinear trend (Juárez-Maldonado et al, 2019). The effect of hormesis has been demonstrated in some works with the technique of seed priming, such as that carried out by Neto et al (2020), where the use of NPs of Fe3O4 in Zea mays produced increased vigor of seedlings to 40 mg L -1 , followed by a decrease to 80 mg L -1 and an increase in this by increasing the dose to 160 mg L -1 . A similar effect was reported in seeds of Allium cepa with applications of 50 to 3200 mg L -1 NZnO (Tymoszuk and Wojnarowicz, 2020).…”
Section: Correlation Analysismentioning
confidence: 99%
“…For example, in Lactuca sativa, the use of Cu, Zn Mn, and Fe NPs favored the germination of seeds (Liu et al, 2016). On the other hand, Fe3O4 NPs increased vigor in Zea mays seeds (Neto et al, 2020). In another study, López-Vargas et al (2020) used carbon and graphene nanotubes in Solanum lycopersicum seeds, increasing the content of chlorophylls, phenols, and total flavonoids in seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, seed priming does not always give a better germinative performance to the seeds, especially when comparing different kinds of priming agents (Esper-Neto et al, 2020). Aluko, Ayodele, Salami, & Olaleye (2020) did not find differences in the T 50 (described as the time required for 50% germination) for seeds treated with NaCl (osmopriming) and aqueous extract of Moringa oleifera leaves (phyto-priming) which were placed to germinate in ideal conditions when compared to the control treatment, as well as no difference was found for the mean emergence time (MET) when the seeds were treated with water and NaCl.…”
Section: Introductionmentioning
confidence: 99%